ANALISIS KARAKTERISTIK NET PRIMARY PRODUCTIVITY DAN KLOROFIL-A DI LAUT BANDA DAN SEKITARNYA - Marpaung, Sartono; Prayogo, Teguh; Yati, Emi; Dwi Purwanto, Anang; Nandika, M. Rizki; Dirgahayu Domiri, Dede; Kushardono, Dony (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2022)
Net primary productivity (NPP) and chlorophyll-a (Chl-a) are indicators of water productivity. In this study, an analysis of NPP and Chl-a characteristics in the Banda Sea was carried out using the Hovmöller diagram and Pearson’s correlation. The NPP data used comes from VGPM and Chl-a from Aqua MODIS satellite. The results of data analysis from January 2003-December 2020, NPP and Chl-a reached highest concentrations in dry season and lowest in wet season. For monthly data, the highest concentrations occurred in August and the lowest in April and December. The waters of the Banda Sea include mesotrophic waters with monthly average of NPP 429 mg C/m2/day and Chl-a 0.24 mg/m3. During La Niña and El Niño, there was a change (decrease/increase) the concentration of NPP and Chl-a in dry season and transition period II. NPP and Chl-a have a high correlation and a strong linear relationship. NPP and Chl-a have almost the same pattern/tendency temporally. The change of NPP concentration temporally corresponded to change of Chl-a concentration. Seasonal factors, La Niña and El Niño have a strong influence in influencing the variability of NPP and Chl-a concentrations. High productivity based on NPP and Chl-a didn’t affect for skipjack and tuna seasons (big pelagic), that occurs in wet season and transition period II. High productivity affects to flying fish season (small pelagic) that occurs in dry season.